The Impact of the Lack of E-1 and E-2 Visa Eligibility on Business and Investment Relations between Uzbekistan and the United States (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article explores the challenges Uzbek entrepreneurs face in obtaining U.S. business visas due to the absence of E-1 and E-2 treaty status. It examines alternative visa options such as L-1, EB-5, and O-1 while highlighting their limitations. The article also discusses the potential benefits of Uzbekistan gaining treaty status and suggests diplomatic and economic strategies to achieve this goal. Strengthening visa opportunities would enhance trade relations and foster economic growth between the two countries.